REPRESENTASI ROMANTISME DALAM PUISI AKU INGIN KARYA SAPARDI DJOKO DAMONO PENDEKATAN STILISTIKA - Elya Sasena; Fika Riyanti; Ika; Rizki Puan Mayang Sari; Saptiana Sulastri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the representation of romanticism in the poem “Aku Ingin” by Sapardi Djoko Damono through a stylistic approach. The research uses a descriptive qualitative method with a stylistic perspective to analyze linguistic elements such as diction, figures of speech, imagery, and language style. The data source is the poem “Aku Ingin”, supported by relevant literature. Data collection techniques include literature study and note-taking by repeatedly reading the poem to identify stylistic elements that represent romanticism. The results show that romanticism in the poem is expressed through simple diction, natural metaphors, and imagery that reflect sincerity and selflessness in love. The poet presents love not in an exaggerated way, but through subtle, symbolic, and meaningful expressions. Thus, romanticism in this poem is characterized by simplicity, emotional depth, and a focus on meaning rather than explicit verbal expression.